STUDI KANDUNGAN C-ORGANIK, KADAR ABU, DAN BOBOT ISI GAMBUT PEDALAMAN DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) TUMBANG NUSA, KALIMANTAN TENGAH - Nina Yulianti; Advenrikus A. Saleilei; Salampak Salampak; Fengky Florante Adji; Zafrullah Damanik; Giyanto Giyanto (Program Pascasarjana Universitas Riau, 2022)
Peatlands is one of carbon stocks in ecosystem. Soil carbon is stored in the peat layer and and the above ground carbon is stored in vegetation. Central Kalimantan has large area of ombrogenic peatland in Indonesia. The aim of this research was; (1) Identify C-organic content, ash content, and bulk density in several peat land uses in KHDTK Tumbang Nusa, Central Kalimantan; (2) Identify the relationship between C-Organic with ash content and bulk density of peat soil. This research was conducted in July 2020 – December 2020. Sampling of peat soil took place in the Tumbang Nusa Special Purpose Forest Area (KHDTK). The analysis of the physical and chemical properties of the soil is located in the laboratory of the Department of Agronomy, Faculty of Agriculture, University of Palangka Raya, the Laboratory of the Research and Development Center for Environment and Forestry (BP2LHK) Banjar Baru, the University Integrated Laboratory. The research was conducted using a sampling method on each different land cover, namely natural forest, burnt areas, and revegetation. Each study site made 3 profiles, then soil samples were taken at a depth of 10 cm, 20 cm, 30 cm, and 40 cm. The results of the study show the conclusions of the results of this study, namely; (1) the largest of C content is 57.83% at secondary forest and the lowest of value of the C content is 54.24% the burnt land. The highest ash content is 9.01% at revegetation area and the lowest ash content is 0.31% at secondary forest land. The highest bulk density is 0.19 g cm-3 at revegetation area and the lowest bulk density is 0.12 g cm-3 at secondary forest. C organic has an inverse relationship with ash content. Further, the relationship between C-Organic and bulk density has a inverse relationship, too.